Digital Communication of PLN UP3 Sibolga in the Dissemination of Public Service Information through Social Media: The Role of Artificial Intelligence and Human Touch - Fadli Febriansyah Zen; Indira Fatra Deni Peranginangin (Ali Institute of Research and Publication, 2026)
This study aims to analyze the digital communication of PLN UP3 Sibolga in disseminating public service information through social media, focusing on the role of Artificial Intelligence (AI) and human touch in public relations practices. While previous studies have examined digital communication and AI in public relations, studies that integrate both aspects in local public service contexts remain limited. This research employs a qualitative descriptive approach, with data collected through in-depth interviews with public relations personnel and documentation of social media content. The results show that digital communication has been utilized to support the dissemination of public service information, with AI functioning as a supporting tool to improve efficiency in content production. However, human involvement remains essential to ensure clarity, empathy, and appropriateness of the message. In addition, digital communication through social media has not fully replaced the public's need for direct communication. Therefore, effective public service communication requires the integration of technological utilization with a humanistic approach to ensure that information is properly understood by the public.